The Impact of Physical Setting on the Development of Street Character (Case Study: Ahmad Yani Street, Tegal) - Ikhsani, Muhammad Azmy; Sari, Suzanna Ratih (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2023)
The development of city facilities and infrastructure is one of the indicators that can be seen to find out how the development of a city area is. The city of Tegal is one of the cities that is currently making improvements in its urban areas, namely by repairing and arranging public spaces in the city of Tegal. One of the results of the improvement and arrangement of public spaces in the City of Tegal is the arrangement of the corridor for Jalan Ahmad Yani, City of Tegal. Ahmad Yani Street in Tegal City is a secondary local road with the status of a city road in the center of Tegal City. Arrangements made on Jalan Ahmad Yani are such as implementing a one-way system for vehicles, providing parking pockets and making improvements to the pedestrian path area. This research will discuss how changes in the physical setting that occurred on Jalan Ahmad Yani after repairs and rearrangements have been carried out so that they affect the formation of a new character and identity of the street space. In addition, this research will also discuss the impact on the community and the environment around Jalan Ahmad Yani from changes in the physical setting. This study uses a qualitative research method with descriptive analysis which aims to explain what phenomena occur in the field and examine based on existing theory. The results of this study are expected to be able to explain how the physical setting of a street space can influence and create character for that street space.